Analisis Struktur dan Sifat Termal Briket Biomassa Terhadap Efisiensi Pembakaran: Analisis Bibliometrik - Silmy, Muhammad Ashbar As; Pramana, Yoddis; Pratama, Wahyu Ridho; Zharif , Erza Arkan; Dharmawangsa, Rafa Adhitya; Septiawan, Bani (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the relationship between material structure and thermal properties of biomass briquettes and their implications for combustion efficiency using a bibliometric approach. Data were collected from Scopus, Web of Science, and Google Scholar databases covering publications from 2015 to 2025. The analysis was conducted using VOSviewer and Bibliometrix to identify research trends, keyword network maps, thematic maps, and contributions by authors and countries. The results indicate a consistent increase in publication trends, with a primary focus on thermal parameters such as calorific value and combustion efficiency. However, structural variables such as density and porosity remain insufficiently explored in an integrated manner. The thematic map further reveals a research gap in linking microstructural characteristics with thermal properties. Overall, this study highlights the importance of a multidisciplinary approach to optimize biomass briquette design as an efficient and sustainable alternative energy source.